1987
DOI: 10.1111/j.1365-2125.1987.tb03254.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of debrisoquine metabolic ratio from hourly urine collections in healthy volunteers.

Abstract: The possibility of simplifying the regimen for the collection of urine samples in the determination of the debrisoquine metabolic ratio (DMR) was explored in 15 normal subjects. In the extensive metaboliser subgroup (EM; n = 11), there was a close correlation between the DMR as determined by an 8 h urine collection and the debrisoquine/4-hydroxydebrisoquine ratio (D/4-OHD) in the hourly samples (excluding the first hour). In the poor metabolisers (PM; n = 4) the phenotype could be identified, but it was not po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The time of drug administration does not affect the phenotype, or the metabolic ratio (Lee, 1988). Indeed, the metabolic ratio is stable from 1 h to at least 24 h after administration of debrisoquine (Philip et al, 1987; Caporaso and Idle suggest that the analytical method used in our study might have biased the results. There is no question of the precision or sensitivity of the combined gas chromatographymass spectrometry (GC-MS) method utilised to determine debrisoquine and its 4-hydroxy metabolite (Murray & Waddell, 1982).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The time of drug administration does not affect the phenotype, or the metabolic ratio (Lee, 1988). Indeed, the metabolic ratio is stable from 1 h to at least 24 h after administration of debrisoquine (Philip et al, 1987; Caporaso and Idle suggest that the analytical method used in our study might have biased the results. There is no question of the precision or sensitivity of the combined gas chromatographymass spectrometry (GC-MS) method utilised to determine debrisoquine and its 4-hydroxy metabolite (Murray & Waddell, 1982).…”
mentioning
confidence: 77%
“…No evidence is provided for this, and indeed the literature would suggest the contrary. The absolute phenotype, as opposed to the metabolic ratio, appears to be a relatively robust parameter and in extensive studies by groups such as Philip et al (1987), Steiner et al (1988 and Lee (1988), as well as by ourselves, it has been possible to demonstrate that the changes to the protocol used by Idle and colleagues do not materially affect the metabolic ratio, let alone the phenotype. These include reducing the dose of debrisoquine from 12.8 mg to 1 mg (Speirs et al, 1986); Idle and his colleagues themselves have shown that there is no saturation of this pathway at doses less than 20 mg in extensive metabolisers (Idle et al, 1978).…”
mentioning
confidence: 99%
See 1 more Smart Citation